An engineering application of the h-p version of the finite elements method to the dynamics analysis of a symmetrical on-board rotor. Issue 5 (2nd September 2016) - Saimi, Ahmed; Hadjoui, Abdelhamid
Abstract: The h-p hybrid finite element method is used in this paper for the dynamic analysis of a symmetrical on-board rotor on mobile dimensionally stable supports. The disc and the bearings are assumed to be rigid, with deformable shaft, the material is isotropic. A three-dimensional beam element is used for the discretization of the rotor. In the standard h-version of the finite element, the used shape functions are cubic Hermit, which respect the boundary conditions in all directions, the shape functions-h are modified so they can make the combination between K-orthogonal polynomial shape functions facilitating combination to use the h-p version of the finite element method. Energy method is used for the determination of energy for the entire rotor system. The equations of motion of the rotor system are determined by the Lagrange method. The calculation steps for linear dynamic behaviour of on-board rotor system analysis are grouped in an application created using MATLAB programming language and validated with the work done previously by the classic version of the finite element method. In this paper, we make a comparison of the natural frequencies of on-board rotor system, obtained by the h-p version of the finite element method with version h.